Validity and Reliability of the Arabic Cough Severity Index - Hamad F. Alrabiah; Nawaf Alqarni; Nuha Alrajhi; Aban Basfar; Tamer A. Mesallam; Mohamed Farahat; Khalid H. Malki (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objectives This study aimed to translate and validate the Cough Severity Index (CSI) into Arabic (A‐CSI) and to evaluate its validity and reliability among patients with chronic cough. Methods This cross‐sectional descriptive questionnaire‐based validation study was conducted at two tertiary hospitals in Riyadh, Saudi Arabia, between December 2023 and August 2024. The CSI was translated from English into Arabic using the forward‐backward method. Its reliability was assessed using Cronbach's alpha and test–retest reliability. Its construct validity was assessed using exploratory factor analysis (EFA), and its internal consistency was assessed using Cronbach's alpha. Its discriminant validity was determined using the Mann–Whitney U test, and its reproducibility was evaluated using the intraclass correlation coefficient (ICC). Results Data were collected from 100 participants, 50 with chronic cough and 50 healthy controls. The mean age was 41.56 ± 14.28 years in the chronic cough group and 35.48 ± 10.02 years in the healthy control group. The A‐CSI exhibited high reproducibility (ICC = 0.896) and excellent internal consistency (Cronbach's alpha = 0.966). EFA identified three factors explaining 66.41% of the variance, with all items having communalities > 0.3. The A‐CSI exhibited significant discriminant validity between the chronic cough and healthy control groups (p < 0.001). Conclusion The A‐CSI is a reliable and valid tool for assessing chronic cough in Arabic‐speaking patients, making it suitable for both clinical practice and research. Level of Evidence Level 3.